Granular Cell Tumor of the Esophagus With Elevated Preoperative Serum Carbohydrate Antigen 19-9: A Case Report - Yanoma, Toru (Int Surg, 2015)
A 59-year-old Japanese man was admitted to our hospital for treatment of a submucosal tumor of the esophagus detected by upper gastrointestinal endoscopy and computed tomography (CT). Endoscopic examination revealed a submucosal tumor in the esophagus 35 cm from the incisor teeth. Biopsy of the lesions identified granular cell tumor. CT indicated a projecting and slightly enhanced homogenous mass measuring 2.0 × 1.5 cm in the esophagus below the tracheal bifurcation. Serum tumor marker studies revealed elevated carbohydrate antigen (CA) 19-9. Therefore, the tumor was considered to have malignant potential, and surgical resection was performed. The final pathologic diagnosis was a benign granular cell tumor, positive for S-100 protein. The patient was doing well with normal CA 19-9 levels and no recurrence more than 5 years after surgery. To the best of our knowledge, this is the first report of a granular cell tumor with elevated serum CA 19-9.